2018
DOI: 10.1038/s41586-018-0183-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic allostery can drive cold adaptation in enzymes

Abstract: Adaptation of organisms to environmental niches is a hallmark of evolution. One prevalent example is that of thermal adaptation, wherein two descendants evolve at different temperature extremes1,2. Underlying the physiological differences between such organisms are changes in enzymes catalyzing essential reactions3, with orthologues from each organism undergoing adaptive mutations that preserve similar catalytic rates at their respective physiological temperatures 4,5. The sequence changes responsible for thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
175
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(183 citation statements)
references
References 37 publications
6
175
0
2
Order By: Relevance
“…Dynamic allostery, an entropy‐tuning mechanism, which remains elusive, has drawn profound research interest . And the gap between “fluctuation‐driven allostery” and the concept of “allosteric pathway” is still unbridged.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic allostery, an entropy‐tuning mechanism, which remains elusive, has drawn profound research interest . And the gap between “fluctuation‐driven allostery” and the concept of “allosteric pathway” is still unbridged.…”
Section: Resultsmentioning
confidence: 99%
“…Dynamic allostery, an entropy-tuning mechanism, which remains elusive, has drawn profound research interest. [76][77][78][79][80][81] And the gap between "fluctuation-driven allostery" and the concept of "allosteric pathway" is still unbridged. A landmark example for dynamic allostery is the Catabolite Activator Protein (CAP), where fluctuations in two from C ij , respectively, which were then analyzed with Equation (8) to give the Z-score of the allosteric site and its ranking in all cavities except the orthosteric site.…”
Section: Allosteric Pathway and The Role Of Dynamic Allosterymentioning
confidence: 99%
“…The interplay between stability and dynamics has been intensively studied in the adenylate kinase (AK) family (11)(12)(13)(14)(15)(16). During the AK catalytic cycle, a reaction that involves reversible phosphoryl transfer (ATP + AMP ↔ 2 ADP), the lid and AMP binding domains undergo coordinated conformational changes that involve local unfolding (12,13,(17)(18)(19), while the core domain remains more rigid and is thought to determine overall thermostability (16,20). Rational design studies have shown that modulation of AK dynamics affect the temperatures where maximal activities are observed (13,16,19).…”
Section: Introductionmentioning
confidence: 99%
“…Mutational studies have also provided evidence that the lid domain may be less tolerant to changes in conformational entropy because the dynamics of this domain have been fine-tuned for substrate binding (19). The AMP binding domain, in contrast, appears more tolerant to enhanced conformational dynamics as local unfolding is thought to control catalytic turnover (19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation